Prevalence of COVID-19 neurological manifestations in patients referred to the Golestan Hospital in Ahvaz between March 2020 to the March 2023 - Mazraeh, Alireza; Azaran, Azarakhsh; Shalilahmadi, Davood; Jalilian, Shahram; Hesam, Saeed (Frontiers in Neurology, 2024)
Due to the abundance of ACE2 receptors in nervous system cells, the SARS-CoV-2 virus can cause damage to this system. This study aims to examine the prevalence of neurological symptoms in COVID-19 patients. In this cross-sectional observational study, 75 COVID-19 positive patients admitted to Golestan Hospital's neurology department in Ahvaz, Iran, from March 2020 to March 2023, were investigated. Neurological clinical symptoms were categorized into three groups: central nervous system, peripheral, and muscular symptoms. The relevant information was collected from patient files, including medical history, imaging data, and laboratory test results. Statistical analysis was performed using SPSS software, employing the rank-biserial correlation coefficient (r), Mann-Whitney U tests, Phi correlation, Cramer's V, and Kendall's Tau to evaluate the prevalence and significance of neurological symptoms. The most common clinical symptoms observed were hemiparesis, dysarthria, Ciguatera Fish Poisoning (CFP), ataxia, and nausea, respectively. Among these symptoms, headaches (P=0.001), seizures (P=0.024), and nausea (P=0.046) were found to be more prevalent in younger patients. Additionally, a significant relationship was identified between the level of serum creatine phosphokinase (CPK) and seizures (P=0.024), with lower levels observed in individuals with vomiting (P=0.024), and higher levels observed in individuals with CFP (P=0.040). This study highlights that patients with COVID-19 may experience serious neurological symptoms. The clinical spectrum and range of neurological symptoms associated with COVID-19 were found to be diverse and extensive, emphasizing the importance of considering this infection as a potential cause of neurological disorders.